Effects of deflection angle on the mechanical properties of constant-resistance, energy-absorbing, and anti-scouring bolts - Tang, Zhi; Wu, Hao; Lv, Jinguo; Chang, Dezhi (Frontiers in Earth Science, 2023)
In order to determine the applicable range of deflection angles for constant-resistance, energy-absorbing and anti-scouring bolts, and providing a reference which design for construction of constant resistance energy absorbing anti-scouring bolts. Principle for the application of constant- resistance, energy-absorbing and anti-scouring bolts with deflection angles is proposed .The effects of deflection angle, impact energy and impact velocity on the deformation performance, load-bearing performance and energy absorption performance of constant- resistance, energy-absorbing and anti-scouring bolts were investigated by numerical simulation.The results show that the deformation process of the bolt with deflection angles changes from axial stretching to "stretching & bending". As the deflection angle increases, the load bearing capacity of the anti-punching device increases, the bolt's breaking force increases after decreasing and then decreases and absorption energy decreases non-linearly. The bolt yield distance decreases while the displacement of bolts basically remain the same and the deflection distance of the anti-punching device decreases. The stroke efficiency of bolts decreases. Based on the design principles of constant-resistance, energy-absorbing and anti-scouring bolt, it was determined that the bolt is still applicable within a deflection angle of 0-17°.The impact energy has a minor effect on the bolt indicators of yield force, breaking force and energy absorbtion, and the bolt's impact resistance time decreases non-linearly with increasing impact energy. Impact velocity has a lower effect on bolt yield force and breaking force. Both yielding time and anti-punching load capacity of bolt decrease with the increase of impact velocity. As the impact velocity increases, yield distance, anti-punching deflection distance and stroke efficiency are all increasing. The absorbtion energy linearly increases with the increase of impact velocity.